PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR FORMAL SISWA DI KELAS X MIA SMAN 1 KUANTAN MUDIK - Novinda, Ledy; Islami, Nur; Zulhelmi, Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Aims of this study is to find the learning result of students' formal thinking ability by applying cooperative learning model with course review horay type on momentum and impulse material in class X SMAN 1 Kuantan Mudik. This research was a quasi experimental research with non-Equivalent control group design. The population of this study was the students of class X MIA and the sample was the students X MIA 3 as the experimental class and the students of X MIA 2 as the control class. Data were obtained and cunducted through the test of the learning outcomes of formal thinking skills before and after applying course review horay model in the experimental class and conventional learning in the control class. Data analysis of this research was appliying a descriptive and inferential method. The results shows that the average score of absorption rate in the pretest of the applying cooperative learning model with course review horay class and conventional class is 39.54% and 40.46% with category of less effective. The average absorption rate in the applying cooperative learning model with course review horay class of posttest score and conventional class is 70.11% in effective category and 51.49% in quite effective category. The increase of students' formal thinking ability (N-Gain) in the applying cooperative learning model with course review horay class is 0.5 in the medium category and the conventional class is 0.17 in low category. T- Test tested obtained p = 0.000 it means p <0.05, then Ho is rejected which means there is a significant difference between the learning result of students' formal thinking ability physics by applying cooperative learning model with Course Review Horay type if compared than conventional learning on the material momentum and impulse at class X MIA SMAN 1 Kuantan Mudik. It can be concluded that the application of course review horay model can be used as an alternative in the learning process in class X MIA SMAN 1 Kuantan Mudik. Keywords: Course Review Horay, formal thinking ability, momentum and impulse